Persepsi Sehat, Asupan Energi, Protein Dan Status Gizi Anggota Rumah Sehat Club Egar - Bingar - Made Intan Puspasari; A.A Agung Ngurah Kusumajaya; I Komang Agusjaya Mataran (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
The direct cause of nutritional status is food and infectious diseases. Energy and protein play an important role in a person's nutritional status because of being the largest contributor in the body Different perception of healthy can affect behavior in determining food selection that is felt appropriate to obtain a healthy body. The purpose of this research is to analyze the relationship between healthy perception with energy intake, protein and nutritional status. This is a cross sectional design study with a sample number of 36 people, with consecutive sampling. Data health perception was collected by using questionnaires. Food recall 2 x 24 hours to know the energy and protein intake. Nutritional Status by weighing weight and measuring height to know the body mass Index (BMI). Data was analysed using univariate and bivariate analyses using the coleration of Spearman rank. The results showed no relationship between healthy perception with energy and protein intake. There was no relationship between energy and protein intake with nutritional status (P = 0.05). Member whose perceptions are likely to be prone to energy intake, protein deficits and have no direct effect on nutritional status. We recommend finding other factors related nutrition and health problems. Keywords: healthy perception, energy intake, protein and nutritional status